Is the Exchange Rate a Shock Absorber? : The Case of Sweden - Thomas, Alun (IMF Working Papers; Working Paper, 1997)
This paper uses a structural vector autoregression representation of the Mundell-Flemming model to analyze the determinants of movements in Sweden's real exchange rate. It finds that, while (supply and demand) shocks account for over 60 percent of the forecast error variance, comparable to several Economic and Monetary Union (EMU) countries, demand shocks account for a higher fraction of these real shocks in Sweden than in those core countries. If real demand shocks result from controllable macroeconomic policies, the cost of relinquishing the exchange rate is no higher, and may be lower, for Sweden than for most core EMU countries.